MULTI-TRACK DIPLOMACY AS INDONESIA'S STRATEGY IN MITIGATING THE COVID-19 PANDEMIC - Firdaus, Aos Yuli (Universitas Nasional, 2020)
At this time, every country, especially since the beginning of 2020, struggles to face the global pandemic, namely COVID-19. Each country has its ways, methods, and strategies for dealing with this pandemic. Indonesia is implementing multi-track diplomacy in its struggle to face COVID-19. The aim of the multi-track diplomacy carried out by the Indonesian government is to increase the medical equipment needed by the Indonesian people and primarily to obtain vaccines for the health of the Indonesian population. Diplomacy in getting this vaccine will be an important issue that continues because all countries will also need the vaccine in the face of this COVID-19 pandemic, which is likely to end for a long time.